A novel kinematic design, analysis and simulation tool for general Stewart platforms. (July 2013) - Inner, Burak; Kucuk, Serdar
In this paper, a general Stewart Platform Simulation tool (STEWSIM) is developed for robot designers and researchers. The STEWSIM uses an efficient connection matrix algorithm that has been developed for kinematic design of all possible types of general Stewart platforms (GSPs), such as 3×3, 3×4, 3×5 … 6×5 and 6×6 with an arbitrary number of legs varying between three and six. This new interactive simulation software based on the MATLAB Graphical User Interface (GUI) provides a suite of analyses, such as inverse and forward kinematics, Jacobian matrix, dexterity, workspace, singularity analysis and trajectory planning, using different kinds of roll-pitch-yaw or Euler angle sets. The STEWSIM also provides the visualization of the GSPs, graphical representation of the workspace, and graphic animation of trajectories specified by inverse kinematics in three-dimensional space. Furthermore, it provides an environment to compare the kinematic performances of the designed GSPs with arbitrary configuration. As a kinematic design, analysis and simulation software, the STEWSIM provides researchers with the ability to change the parameters interactively for designing their manipulators with optimum specifications, such as leg lengths and attachment points. The usage of this simulation tool may result in new types of feasible robotic manipulators that can be used for practical applications in industry.